Jejak Okupasi Manusia Prasejarah di Situs Gua Batu Baras, Kalimantan Selatan - Fajari, Nia; Alifah; Wasita; Ulce Oktrivia; Eko Herwanto; Fatom Ahmad; Muhammad Lanang Adiyatma; Thomas Suryono; Reynaldi Saputra (PURBAWIDYA, 2024)
Batu Baras Cave, located in Bangkalan Dayak Village, is an archaeological site in the limestone hill area of ​​Kotabaru Regency, South Kalimantan. Kalimantan prehistoric times have not been established as well as in Java. Recent publications reveal human occupation in the Preneolithic-Paleometallic period in the Kotabaru karst, including in Batu Cave, Cililin Cave 1, Jauharlin Cave 1, and Batu Baras Cave. This article describes the variability of archaeological findings to reveal that human occupation occurred in Batu Baras Cave. Morphological and stylistic analysis aims to illustrate the variety of archaeological data found. We used several approaches to compile the interpretation, including zooarchaeology, paleoanthropology, and spatial. Our result reveals that human occupation in Batu Baras Cave occurred in the early Prenolithic-Neolithic period in 12,402-4,230 calBP. Batu Baras Cave became a dwelling and burial site for the Australomelanesid population in the Preneolithic. The Austronesians inhabited Batu Baras Cave in the Neolithic.